સમીકરણ $\sqrt {(x + 1)} - \sqrt {(x - 1)} = \sqrt {(4x - 1)} $, $x \in R$ ને .. . .

  • A

    એક ઉકેલ

  • B

    બે ઉકેલ

  • C

    ચાર ઉકેલ

  • D

    એકપણ ઉકેલ શક્ય નથી

Similar Questions

જો $x = 3 - \sqrt {5,} $ તો ${{\sqrt x } \over {\sqrt 2 + \sqrt {(3x - 2)} }} = $

${{\sqrt 2 } \over {\sqrt {(2 + \sqrt 3 )} - \sqrt {(2 - \sqrt 3 } )}} = $

જો ${\left( {{2 \over 3}} \right)^{x + 2}} = {\left( {{3 \over 2}} \right)^{2 - 2x}},$ તો $x =$

જો ${a^{x - 1}} = bc,{b^{y - 1}} = ca,{c^{z - 1}} = ab,$ તો $\sum {(1/x) = } $

${a^{1/3}} + {a^{ - 1/3}}$ નો સંમેય કારક અવયવ મેળવો.